2010
DOI: 10.2460/javma.237.4.378
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of adjunctive tetracycline treatment on refractory corneal ulcers in dogs

Abstract: Topical tetracycline ophthalmic ointment was a safe, inexpensive, and effective adjunctive treatment for refractory corneal ulcers in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
3
40
0
2
Order By: Relevance
“…The age range of affected horses in this cohort (3–24 years) is similar to that previously reported (2–27 years and 3–28 years), as is the mean age (12 years vs. 13.7 years and 13.7 years) . This is in contrast to dogs, in which SCCEDs typically manifests in older animals (considering their comparatively shorter canine lifespan), with published means ranging from 8.7 to 9.4 years . Although not identified in horses in this study, the potential correlation between older patients and an increased incidence of nonhealing, corneal ulcers might be associated with age‐related changes in the corneal epithelial basement membrane.…”
Section: Discussionsupporting
confidence: 85%
“…The age range of affected horses in this cohort (3–24 years) is similar to that previously reported (2–27 years and 3–28 years), as is the mean age (12 years vs. 13.7 years and 13.7 years) . This is in contrast to dogs, in which SCCEDs typically manifests in older animals (considering their comparatively shorter canine lifespan), with published means ranging from 8.7 to 9.4 years . Although not identified in horses in this study, the potential correlation between older patients and an increased incidence of nonhealing, corneal ulcers might be associated with age‐related changes in the corneal epithelial basement membrane.…”
Section: Discussionsupporting
confidence: 85%
“…Classic histopathologic features include nonadherent, dysplastic epithelium adjacent to the ulcerated region, loss of epithelial basement membrane, presence of a hyalinized, acellular zone in the superficial stroma, and an abnormal nerve plexus in the anterior stroma surrounding the erosion 6 . Affected dogs are typically middle aged and free of concurrent ocular disease, and Boxers have been demonstrated to be overrepresented in multiple studies 1–3,5,7,8 . A variety of medical and surgical treatments have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The population of dogs from which study subjects were enrolled was similar to those of previous studies 4,13,14,16 involving dogs with SCCED, with middle-aged dogs and the Boxer breed overrepresented in both treatment groups. Treatment groups were similar to each other with respect to distributions of sex, age, neuter status, and affected eye.…”
Section: Discussionmentioning
confidence: 75%
“…In a placebo-controlled study 15 of dogs with nonhealing corneal erosions, topical administration of epidermal growth factor improved healing rate, but the concentration of epidermal growth factor at the ocular surface in those dogs was not determined. Another investigation g revealed a low tear concentration of transforming growth factor β in dogs with SCCED; in a subsequent study, 13 topical and oral administration of tetracyclines had a positive effect on healing of SCCEDs, putatively through the modulation of growth factors including transforming growth factor β. In another study, 48 high concentrations of nerve growth factor were identified in the tears, corneas, and lacrimal glands of dogs with experimentally induced corneal wounds, but topical application of additional exogenous nerve growth factor failed to accelerate reepithelialization.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation